FROM PEACE AGREEMENT TO POLITICAL ARENA: WOMEN’S PARTICIPATION IN POLITICS AFTER 15 YEARS OF THE MOU HELSINKI IN ACEH - Teuku Muzaffarsyah; Bobby Rahman; Naidi Faisal; Fidhia Aruni; Rifki Elindawati (Politik Indonesia: Indonesian Political Science Review, 2025)
The Helsinki MoU is the peace agreement signed on August 15, 2005, between the Government of the Republic of Indonesia and the Free Aceh Movement (Gerakan Aceh Merdeka, GAM) in Helsinki, Finland. In the context of political participation, the MoU urges Acehnese to increase women's participation in politics through affirmative action, particularly a 30% quota in legislative bodies. However, after 15 years of the MoU, Acehnese women’s participation in politics is still yet far from the quota. Thus, this study aims to examines the effectiveness affirmative action policy through the landscape of gender and the persistent gaps between policy intent and outcomes. This study used a qualitative reseach method with post-positivist approach. The data were collected through in-depth interviews with members of the Aceh People’s Representative Council (Dewan Perwakilan Rakyat Aceh, DPRA), political party representatives, and women's empowerment officials. The secondary sources were derived from legislation, reports, and media. Findings reveal persistent structural, cultural, and institutional barriers, such as patriarchal norms, limited political support, insufficient resources, and weak institutional enforcement—that hinder the effectiveness of affirmative action policies. As the result we found that while legal frameworks exist, the actual empowerment of women in Aceh’s political sphere remains constrained and symbolic.